The Fight Against Digital Hate Speech: Disentangling the EU’s Regulatory Approach and Hurdles - Evangelia Psychogiopoulou (German Law Journal)
Digital platforms and social media have expanded the ways in which individuals can exercise their right to freedom of expression and obtain and diffuse information. At the same time, they have become a principal means for haters to express and spread their hate in ways that would have been unthinkable some years ago. Responsive to the challenge, the EU has progressively developed a broad range of instruments and tools to counter online hate speech. This chapter discusses the key characteristics of the EU arrangements made to fight digital hate speech, shedding light on what is a multi-faceted and daunting regulatory task.